Case studies and analyses of soft clay consolidation accelerated by prefabricated vertical drains - Jia, Yin (2014)
In the recent years, more reclaimed land has been constructed to meet the demands of rapid urbanization. During the construction of reclamation works, prefabricated vertical drains (PVDs) with preloading are widely used to increase the shear strength of soil and shorten construction schedule.